The Effect of Digtogloss Technique on Students’ Writing Skill - Safinatun Najjah; Saiful Marhaban; Tengku Maya Silviyanti (Universitas Syiah Kuala, 2021)
Writing is one of the language skills that is considered hard to master by students. Based on the preliminary research that was done at Mtsn 8 Aceh Besar, it revealed that the students’ average score in writing were still low. Therefore, in order to help students to improve their writing skill, dictogloss technique which was introduced by Wajnryb in 1990 is claimed as a technique which gave good effect on students’ writing skill. The objective of this research is to find out the effect of dictogloss technique on students’ writing skill using library research as the method of the research. Thus, the data was collected from previous studies related to dictogloss technique and paraphrased to get information about dictogloss technique. Based on the result of this research, it showed that dictogloss technique had positive effect on students’ writing skill. Moreover, several studies revealed that the students gave positive attitudes towards the use of dictogloss technique. In addition, dictogloss technique also encouraged and motivated students during the process of teaching and learning.